Audio Visual sebagai Media dalam Pengajaran Keterampilan Menulis Esai Deskriptif: Audio Visual as a Medium in Teaching Descriptive Essay Writing Skills - Esti Kurniasih (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2010)
This research describes (1) the implementation of audio visual as a medium for teaching descriptive essay writing and (2) the difficulties encountered by the lecturer when applying audio visual as a teaching medium. The results generally showed that the implementation of audio visual did not run optimally. This was caused by three factors: the classroom setting for Writing II, obstacles faced by the lecturer and students, and inappropriate timing for data collection. Meanwhile, the lecturer's difficulties included: (1) limited time for essay development; (2) inappropriate timing for data collection; (3) an unsuitable classroom environment; (4) the use of two small speakers; and (5) overly bright lighting that made it difficult to see the images clearly. Penelitian ini mendeskripsikan (1) implementasi audio visual sebagai media dalam pengajaran menulis esai deskriptif dan (2) kesulitan yang dihadapi dosen saat menerapkan audio visual sebagai media pengajaran. Hasil penelitian secara umum menunjukkan bahwa implementasi audio visual tidak berjalan dengan baik. Hal ini disebabkan oleh tiga faktor, yaitu tempat pelaksanaan mata kuliah (Writing II), kendala yang dihadapi dosen dan mahasiswa, serta waktu pengambilan data yang kurang tepat. Sementara itu, kesulitan yang dialami dosen meliputi: (1) waktu terbatas untuk pengembangan esai; (2) waktu pengambilan data yang tidak tepat; (3) ruang kelas yang kurang sesuai; (4) penggunaan dua speaker kecil; dan (5) pencahayaan kelas yang terlalu terang sehingga gambar sulit dilihat dengan jelas.